The Legally Accountable Person: Conditions and Stages of Legal Capacity in Islamic Jurisprudence: المحكوم عليه : شروط وأدوار الأهلية في التشريع الإسلامي - Mahmood, Dr. Sajid (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
In Islamic jurisprudence, a person becomes legally accountable (a mukallaf) and subject to religious obligations only upon meeting two core conditions: reaching puberty and being of sound mind. This responsibility is structured around two types of legal capacity: the Capacity for Obligation (the basic right to have rights, granted from birth) and the Capacity for Action (the legal validity of one's deeds, which develops over time). This framework unfolds across four life stages: the prenatal stage (limited rights), infancy (rights managed by a guardian), the age of discernment (partial validity for actions), and finally adulthood, where full mental and legal competence is achieved, making one fully responsible. The system humanely addresses exceptions, exempting the insane or intoxicated from direct duty and placing financial responsibilities for children's wealth upon their guardians. Ultimately, Islamic law demonstrates its profound justice by meticulously aligning religious responsibility with an individual's natural physical and mental development.